Spatial and temporal dynamics of exuberant colour polymorphism in the southern cricket frog. Issue 35 (16th September 2020) - Cox, Christian L.; Bowers, Jessica; Obialo, Chinonye; Curlis, John David; Streicher, Jeffrey W.
ABSTRACT: Intraspecific variation in colour pattern is widespread across multitudinous amphibian species. In some species, many distinct colour patterns are maintained within populations, a phenomenon referred to as exuberant colour polymorphism. The underlying causes of exuberant colour pattern polymorphism are poorly understood but are likely explained by selection, rather than neutral processes like genetic drift. Nevertheless, empirical data are needed to understand the selective drivers of this phenomenon, but such data are currently lacking for most polymorphic species. We studied frequency, spatial, and linkage dynamics of colour pattern across nine populations of the southern cricket frog ( Acris gryllus ) from southeastern Georgia, USA. Using 233 individuals, we combined direct field observations with examination of natural history specimens to look at colour pattern characteristics as they relate to space, time, and sex over a 30-year time frame. We found evidence of spatial and temporal variation in colour pattern across populations. We also discovered associations among colour pattern traits and between two colour pattern traits and sex. Our results suggest that the exuberant colour polymorphism of A. gryllus may involve correlations between traits and be caused by spatial and/or temporal variation in selection. However, similar studies in other species are necessary to allow us to discriminate among different drivers of colour pattern in exuberantly polymorphic frogs. Collectively, such systems offer important opportunities for understanding the evolution of colour and phenotypic diversity.